EFEK PENGGUNAAN OBAT ANTIDIABETES TERHADAP LUARAN TERAPI PASIEN DIABETES MELITUS TIPE 2 KOMPLIKASI RETINOPATI DIABETIK DI RSUP SANGLAH DENPASAR - Sukarmini, Nyoman Fabby (Jurnal Farmasi Udayana, 2019)
Diabetic retinopathy (DR) is a microvascular complication of DM caused by damage to blood vessels in the retina and can cause permanent blindness. Good blood glucose control has been shown to reduce DR onset and risk of development. The purpose of this study was to determine the use of antidiabetic drugs in patients with DM type 2 complication DR and outcomes therapy seen from changes in blood glucose levels and degrees of DR. The design of this study was observational with retrospective data collection obtained from the medical record of patients type 2 DM complication DR from January 2018 to December 2018 in Sanglah General Hospital. Characteristic of patient and DR degrees were analyzed descriptively while changes in blood glucose levels for 6 months were analyzed with statistic (paired t-test and Wilcoxon). In this study, 29 patients were included consisted of 14 patients (48.3%) used insulin, 9 patients used OAD (31.0%) and 6 patients used combination OAD + insulin (20.7%). The mean KGDP of patients decreased significantly (p<0.05) in the OAD, insulin and combination OAD + insulin groups respectively 52.22±20.34; 58.85±19.29 and 92,83±26,99 mg/dL. The mean KGD2PP of patients decreased significantly (p<0.05) in the OAD and insulin groups respectively 69.00±23.22 and 79.35±31,58 mg/dL, but in the combination OAD + insulin group, reduction that occurred was not significant (p>0.05) which was 67,33±49,55 mg/dL. The mean HbA1c decreased significantly (p<0.05) in the OAD, insulin and combinations OAD + insulin group respectively by 1.77±0.39, 1.58±0.52 and 1.60±0,55 %. Increased degree of RD occurs in 5 of 29 (17.24%.) Keywords: Type 2 diabetes mellitus, Diabetic retinopathy, Blood glucose, OAD, Insulin